2008
DOI: 10.1039/b713274c
|View full text |Cite
|
Sign up to set email alerts
|

Mid-IRspectra of different conformers of phenylalanine in the gas phase

Abstract: The experimental mid-and far-IR spectra of six conformers of phenylalanine in the gas phase are presented. The experimental spectra are compared to spectra calculated at the B3LYP and at the MP2 level. The differences between B3LYP and MP2 IR spectra are found to be small. The agreement between experiment and theory is generally found to be very good, however strong discrepancies exist when -NH 2 out-of-plane vibrations are involved. The relative energies of the minima as well as of some transition states conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…As the number of water molecules is increased, the bridge becomes longer. [9] Meijer and coworkers [10] reported mid-and far-IR spectra of six conformers of phenylalanine in the gas phase and they have found good agreement between experiment and theoretical spectra. The conformational behavior and IR spectrum of L-phenylalanine by matrix-isolation IR spectroscopy and DFT calculations showed that the 14 most stable structures which differ in energy by less than 10 kJ mol À1 , and the entropy also plays an essential role in determining the relative abundance of the possible low-energy conformational states in phenylalanine.…”
Section: Introductionmentioning
confidence: 69%
“…As the number of water molecules is increased, the bridge becomes longer. [9] Meijer and coworkers [10] reported mid-and far-IR spectra of six conformers of phenylalanine in the gas phase and they have found good agreement between experiment and theoretical spectra. The conformational behavior and IR spectrum of L-phenylalanine by matrix-isolation IR spectroscopy and DFT calculations showed that the 14 most stable structures which differ in energy by less than 10 kJ mol À1 , and the entropy also plays an essential role in determining the relative abundance of the possible low-energy conformational states in phenylalanine.…”
Section: Introductionmentioning
confidence: 69%
“…The low intensity of the observed spectra and the non-observation of the conformers, detected with other techniques, can be caused by ionization and photofragmentation processes during laser ablation taking place with different rates for the different conformers. Kim and co-workers [145][146][147], from their measurements of the ionization energies (IE) of the low-energy conformers of phenylalanine, affirm that the observed conformers IIa and IIb have higher IEs than the other conformers.…”
Section: Phenylglycine and Phenylalaninementioning
confidence: 76%
“…3.3). Vibrational couplings make the interpretation less easy, and confident assignments rely on a large spectral range (the whole amide I-III regions), especially when spectral resolution is limited, usually 1% of the IR frequency for a freeelectron source [48,54,55,66,69,79,80,82,83,95,97,105,108,131,132,136,141,142]. Difference frequency generation from table-top OPOs [52,64,90,104,120,126,127,137,139,144,145] has become a valuable alternative source to FELs, providing spectral resolutions in the cm À1 range, and solid conformational assignments have emerged from studies combining amide I/II and amide A spectral ranges (Fig.…”
Section: Methodsmentioning
confidence: 99%